The Impact of Learning Motivation and Facilities for the Result of Social Subject in SMP Negeri 7 Pematang Siantar - Chaterine Angel Natalia; Sotarduga Sihombing; Injen Pardamean Butarbutar (MultiTech Publisher, 2023)
The problem in this research is the low results of students' social studies learning in the learning process. This research aims to determine the influence of motivation and learning facilities on the learning outcomes of class VIII students in social studies subjects at SMP Negeri 7 Pematang Siantar. The variables in this research are learning motivation and learning facilities as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research, with the research population being Class VIII students of SMP Negeri 7 Pematang Siantar for the 2023/2024 academic year, consisting of 7 classes with a total of 223 students and a research sample of 1 46 students of Class VIII SMP Negeri 7 Pematang Siantar in total. Simple random sampling. Data collection techniques use instruments: (1) Learning Motivation questionnaire , (2) learning facilities questionnaire , and (3) learning outcomes questionnaire. The results of this study show that: (1) there is a positive and significant influence of parental income on learning outcomes . This result can be seen in the t test where the t value is calculated learning motivation , namely showing the tcount value > ttable (3,382 > 1.655) and significant value (0.001 < 0.05), which means that this variable is significant. (2) there is a positive and significant influence of learning facilities on learning outcomes, this result can be seen in the t test where the calculated t value of the learning facilities shows the t calculated value > ttable (2,240 > 1.655) and significant value (0.027 < 0.05) which means that this variable is significant. (3) parental income and learning facilities jointly influence learning outcomes, these results can be seen in the F test where the calculated F value shows the calculated f value > ftable (5.776>3.06) and significant value (0.004 < 0.05). The R Square coefficient of determination test was found to be 0.07 5 , which means that 7.5 % of the variables of parental income and learning facilities have an influence on student learning outcomes at SMP Negeri 7 Pematang Siantar and the remaining 92.50 % is the influence of other variables that are not examined in this research.